1982
DOI: 10.2343/geochemj.16.51
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence of paleowaters in the Po sedimentary basin (Northern Italy).

Abstract: Stable isotopic composition and radiometric age were measured for groundwaters in the Emilia area of the Po sedimentary basin (Northern Italy). Waters from uncontmned shallower aquifers, deep circulating continental waters and sodium chloride waters (relic waters) squeezed out from underlying marine forma tions during past geological events were considered. Waters from supposed confined aquifers (paleowaters) are usually depleted in 0-18 (61'0 < -10° o) and their 6180-6D relationships are not consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…7). Waters from the upper unconfined aquifer (Group A) have temperatures ranging from 10.8 and 15.2°C, very close to the annual mean of the surface air temperature of the study area (13.5°C, Gorgoni et al, 1982 and S. Felice sul Panaro meteorological station data available at: http://dexter-smr.arpa.emr.it) and show circum neutral pH between 6.7 and 7.5. TDS values are highly variable (from 512 to 3168 mg/L) while positive Eh values (with the exception of sample 16) denote oxidizing conditions in the leached strata.…”
Section: Chemical and Isotopic Composition Of Watersmentioning
confidence: 87%
See 1 more Smart Citation
“…7). Waters from the upper unconfined aquifer (Group A) have temperatures ranging from 10.8 and 15.2°C, very close to the annual mean of the surface air temperature of the study area (13.5°C, Gorgoni et al, 1982 and S. Felice sul Panaro meteorological station data available at: http://dexter-smr.arpa.emr.it) and show circum neutral pH between 6.7 and 7.5. TDS values are highly variable (from 512 to 3168 mg/L) while positive Eh values (with the exception of sample 16) denote oxidizing conditions in the leached strata.…”
Section: Chemical and Isotopic Composition Of Watersmentioning
confidence: 87%
“…As a whole, no hints of thermal anomalies have been detected in the studied aquifers, as occur elsewhere in the Po Plain in areas crossed by faults and/or fault systems as well as where structural highs have been recognised at depth (Chiaramonte and Novelli, 1985;Conti et al, 2000;Gorgoni et al, 1982;Federico et al, 2008). Indeed, starting from the annual mean of the surface air temperature, water temperatures are in general agreement with the vertical gradient measured in deep exploration wells or inferred in the area in/for the first 900 m depth from geological, geothermal and structural consideration, equals 3°C/100 m (Gorgoni et al, 1982).…”
Section: Chemical and Isotopic Composition Of Watersmentioning
confidence: 90%
“…(continued) the Po plain, Italy (Gorgoni et al, 1982) not reported in Table 1. The few tritium data support a long-term circulation at depth (Gorgoni et al, 1982;Toscani et al, 2001). The waters reported in Table 1 may be distinguished into two main groups:…”
Section: Main Geochemical Features and Genetic Hypothesesmentioning
confidence: 99%
“…NaCW may have both high (e.g., Larderello geothermal field, central Italy: Duchi et al, 1992) and low temperature (e.g., Northern Apennines, Italy: Toscani et al, 2001; Po plain, Italy: Gorgoni et al, 1982) and salinity. Salinity may range from very low (e.g., some waters from the Gotthard Tunnels, Switzerland: Michard et al, 1966) up to some hundred of milliequivalent/L (mEqle/L) of total dissolved ions (Σions) (e.g., waters from Gambassi and Casciana, Central Italy: Bencini et al, 1977).…”
Section: Main Geochemical Features and Genetic Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation